Pertanggungjawaban Atas Kerugian Konsumen pada Jasa Titip Produk Luar Negeri Perspektif Fatwa DSN-MUI No. 112/DSN-MUI/IX/2017 Tentang Akad Ijarah - Rizka Fadila; Cahaya Permata (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The service of entrusting foreign products is a business phenomenon that is growing rapidly in Indonesia, but still causes problems, including losses experienced by consumers. Due to the confiscation of overseas entrusted service products by the Immigration authorities. This research aims to analyze liability for consumer losses in overseas product entrustment services in terms of statutory regulations and the DSN-MUI Fatwa. This type of research is normative juridical with a conceptual approach and statutory regulations, data is collected through document study, data is processed and analyzed qualitatively. The results of this research show that liability for consumer losses according to the Consumer Protection Law requires jastipers to provide compensation to consumers. Regulation of entrusted services can refer to the Trade Law, ITE Law, Government Regulations on Trade Through Electronic Systems and the Consumer Protection Law. Meanwhile, in the perspective of the DSN-MUI fatwa regarding the Ijarah contract, responsibility for consumer losses refers to the provisions on rental benefits in compensation if Al-Ta'addi, Al-Taqshir and Mukhalafat al-Syuruth are carried out. Integration between statutory regulations and fatwas is needed to increase consumer protection and encourage responsible business practices in the foreign product delivery service industry.